SPECIES COMPOSITION AND DISTRIBUTION OF SEAWEEDS FROM SOME SMALL ISLANDS (NAM YET, SON CA, SONG TU TAY, SINH TON) OF TRUONG SA ARCHIPELAGO - Tien, Dam Duc; Cuong, Do Huy (Vietnam Journal of Marine Science and Technology, 2016)
Marine algae are one important component of marine resources. Different compounds such as agar, alginat, carrageenan, biological activities can be extracted from marine algae … They have been used in fields as follows: fabric weave, refresher, medicine, ... Nam Yet, Son Ca, Song Tu Tay and Sinh Ton are small islands of Truong Sa archipelago in Truong Sa district, Khanh Hoa province, Central Vietnam. This paper presents results on species composition and distribution of seaweeds at Nam Yet, Son Ca, Song Tu Tay and Sinh Ton islands of Truong Sa archipelago. The study results show that at four islands we recorded 133 species of marine seaweeds that belong to four divisions: Cyanophytes, Rhodophytes, Phaeophytes and Chlorophytes. Among them, 13 species are classified into Cyanophytes (comprising 10.0% of total species); 67 species into Rhodophytes (50.3%); 20 species into Phaeophytes (15.0%) and 33 species into Chlorophytes (24.7%). The distribution of marine seaweeds from Nam Yet, Son Ca, Song Tu Tay and Sinh Ton islands show significant differences as follows: 34 species (Son Ca island) to 77 species (Nam Yet island) and the average value is 57.3 species per island. Homogeneous coefficient oscillates from 0.30 (Nam Yet and Sinh Ton) to 0.49 (Son Ca and Sinh Ton) and the average value is 0.39. The current investigations show that 75 species were collected in the littoral zone (56.4%), 28 species in sub-littoral zone (28.0%) and 30 species in sub-littoral and littoral zone (15.6%).